Early prognosis prediction in acute myeloid and acute lymphoid leukemia patients using cell-free DNA concentration ratios - George, Noreen Grace; Rishi, Bhavika; Singh, Amitabh; Vishmaya, Sree; Kumar, Rakesh; Kushwaha, Neetu; Kaur, Manpreet; Bhardwaj, Reena; Jain, Ankur; Jain, Aditi; Chaudhry, Sumita; Misra, Aroonima (Frontiers in Molecular Biosciences, 2024)
Background: Cell-free DNA (cfDNA) is a promising biomarker for disease prediction in many cancers, including acute leukemia (AML and ALL). This study investigated the role of cfDNA in predicting relapse or unfavorable outcomes in acute leukemia patients upon initial diagnosis.Paired peripheral blood samples of 25 patients with ALL and AML were compared at baseline, induction/followup, and clinically correlated with clinicopathological and outcome variables according to risk category. CfDNA was isolated using commercial cfDNA extraction kits. The probability of poor outcomes in high-risk groups and a cut-off value for risk stratification minimal residual disease (MRD) positivity and MRD positivity and outcome prediction were derived.Results: Twenty-five patients diagnosed as AML and ALL were risk stratified based on NCI risk stratification and out of these 25 patients-four patients were of standard risk (SR), one patient was Intermediate risk (IR) while a majority of patients (80%) were high risk (HR) patients. Of these four HR patients ended up in mortality. The ratio of cfDNA reduction at baseline at the end of induction was a strong predictor of poor outcomes in high-risk patients, regardless of MRD status. A cfDNA ratio score of 2.6 or higher at diagnosis/remission predicted poor outcomes, with higher accuracy than conventional MRD detection by flow cytometry.A higher cfDNA ratio at diagnosis/remission or at baseline cfDNA predicts poor outcomes in acute leukemia patients. This pilot study suggests that cfDNA ratio scoring may be a useful tool for predicting prognosis in acute leukemia patients, regardless of MRD status.